"BioVenture: Desafio Biológico" - Learning Biology Through an Interactive Digital Game - de Miranda, Caio da Silva; Yamanaka, Caroline; Bastos, Fábio; Oda, Álvaro; Sousa, Pedro Moises de (Anais do Workshop de Sistemas de Informação (WSIS), 2024)
This article presents the development, application and evaluation of the educational game "BioVenture: Desafio Biológico", created on the Unity platform. The game aims to help students learn science and biology, allowing 7th graders to learn about the impact of human actions on the environment through interactive questions and answers while exploring an open world experiencing ecological imbalance. The game was evaluated through a usability test with children, showing positive results in terms of the learning experience and the effectiveness of the game as an educational tool, promoting effective learning and the development of essential skills.